Black wolves - Elliott, Kate, 1958- (Black wolves trilogy, 2015)
SOME CHOICES CAN NEVER BE UNDONE. He lost his honor long ago. Captain Kellas was lauded as the king's most faithful servant until the day he failed in his duty. Dismissed from service, his elite regiment disbanded, he left the royal palace and took up another life. Now a battle brews within the palace that threatens to reveal deadly secrets and spill over into open war. The king needs a loyal soldier to protect him. Can a disgraced man ever be trusted?